Population genetic structure of blue swimming crab (Portunus pelagicus) in the Gulf of Thailand - VERAKIAT SUPMEE; AMONSAK SAWUSDEE; PRADIT SANGTHONG; JUTHAMAS SUPPAPAN (Society for Indonesian Biodiversity, 2020)
Abstract. Supmee V, Sawusdee A, Sangthong P, Suppapan J. 2020. Population genetic structure of Blue Swimming Crab (Portunus pelagicus) in the Gulf of Thailand. Biodiversitas 21: 4260-4268. The Blue Swimming Crab (Portunus pelagicus) is an important commercial fishery product in the Gulf of Thailand. To provide a strategy for management, information on genetic features is needed. In our study, the population genetic structure and demographic history of the P. pelagicus living in the Gulf of Thailand were analyzed based on the variation of the nucleotide sequence of the mitochondrial DNA in the control region (mtDNA CR). Ninety-seven samples were collected from 5 sampling sites: Rayong, Chonburi, Chumphon, Surat Thani, and Nakhon Si Thammarat provinces in the Gulf of Thailand. Forty-nine haplotypes were identified and 39 private haplotypes were found. An AMOVA showed no genetic structure among populations. The pairwise FST also indicated no statistically significant difference between all possible regional combinations. The topology of a minimum spanning network revealed a star-like topology that was not separated by geographic structure. The historical demographic analysis revealed a stable population size for a long period and followed by a very recent expansion. An absence of a population structure of the P. pelagicus was possibly caused by a high level of gene flow. The results of this study differ from previous studies that used genetic markers in nuclear DNA. Thus, to clear the genetic structure information of P. pelagicus in the Gulf of Thailand, we suggested that more sensitive markers to detect genetic structure should be used in further analysis.